Lehre, Fort- und Weiterbildung in Public Health: Ergebnisse der AG 9 des Zukunftsforums Public Health, Berlin 2016 = Education and training in Public Health : results of the working group 9 of the forum Future Public Health, Berlin 2016 - Dragano, Nico; Schneider, Sven (Das Gesundheitswesen, 2017)
The need for a qualified public health workforce can only be met by appropriate provision of a wide spectrum of basic, advanced and continuing education and training programs on public health that meet international standards. At the same time, efforts must be made to offer young academics attractive career opportunities. Training in public health competences must also be provided for allied professionals in health care and for professions with influence on the determinants of health such as urban planning or agricultural science. This report from a working group meeting at the ‘Public Health Zukunftsforum 2016’ in Berlin presents ideas for the further development of training in public health in Germany.